Effect of whey protein concentrate and sodium chloride concentrations on the odour profile of sous vide cooked whole-muscle beef from Argentina - Grigioni, Gabriela Maria; Langman, Leandro Ezequiel; Irurueta, Martin; Vaudagna, Sergio Ramon; Szerman, Natalia (Elsevier, 2019)
Semitendinosus muscles added with whey protein concentrate (WPC) and sodium chloride (NaCl) were submitted to sous vide cooking. Four enhancement treatments and a control were tested: 0.875% WPC (w/w) + 0.625% NaCl, 2.625% WPC + 0.625% NaCl, 0.875% WPC + 1.875% NaCl, 2.625% WPC + 1.875% NaCl, and control (non-injected muscles). Odour analyses were carried out with an electronic nose (EN) system. EN data were evaluated applying Principal Component Analysis, Linear Discriminant Analysis and Partial Least Squares algorithm. EN was able to discriminate the odour profiles of cooked enhanced beef as a function of the amount of WPC added. No significant differences in odour profiles were observed regarding NaCl concentration. These results agreed with those obtained when odour profiles were analysed in WPC dispersions. The reported results support the applicability of EN methodology for analysing the impact of processing parameters on beef odour profiles.